IMPLEMENTATION OF THE AUTHORITY OF THE HEALTH CENTER FOR SUPERVISION OF CHILDREN'S INTELLIGENT PROPERTY - Bernardo da Cruz (Jurnal Hukum Khaira Ummah, 2022)
Article 369 of the Civil Code states that if guardianship is ordered by a judge, the clerk at the court concerned must immediately notify by letter of the appointment to the Heritage Hall with a statement. However, not all courts send copies of the existence of guardianship to the Balai Harta Peninggalan. This research is a normative juridical research using secondary data which is supported by primary data in the field. The results of the analysis are presented descriptively. Field data were taken through interviews with the Chair and Secretary at the Balai Harta Peninggalan Semarang. As for the authority of the Balai Harta Peninggalan in supervising the property of minors, it is that the task of the Balai Harta Peninggalan in supervising the guardian's duties does not run properly, especially because there is no synchronization between implementation and the regulations that govern it , where there is a lack of cooperation between relevant agencies, such as the District CourtKeywords: Trust, Heritage Hall, Supervisory Guardian.